2019
DOI: 10.3390/v11111027
|View full text |Cite
|
Sign up to set email alerts
|

Viromics Reveal a Number of Novel RNA Viruses in Swedish Mosquitoes

Abstract: Metagenomic studies of mosquitoes have revealed that their virome is far more diverse and includes many more viruses than just the pathogenic arboviruses vectored by mosquitoes. In this study, the virome of 953 female mosquitoes collected in the summer of 2017, representing six mosquito species from two geographic locations in Mid-Eastern Sweden, were characterized. In addition, the near-complete genome of nine RNA viruses were characterized and phylogenetically analysed. These viruses showed association to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 40 publications
(51 reference statements)
1
35
0
Order By: Relevance
“…In agreement with previous virome studies, most of the taxa derived from honey-baited FTA cards have been identified in various invertebrates [39] and associated to mosquitoes [40]. Additionally, mosquito-specific viruses detected in FTA cards (Table 2) have been described as part of the viral communities harbored by several mosquito species in different geographic regions [41][42][43][44][45][46][47][48]. Bold type corresponds to the selected viruses for primers design.…”
Section: Virome Composition On Honey-baited Fta Cards During Entomolosupporting
confidence: 86%
See 2 more Smart Citations
“…In agreement with previous virome studies, most of the taxa derived from honey-baited FTA cards have been identified in various invertebrates [39] and associated to mosquitoes [40]. Additionally, mosquito-specific viruses detected in FTA cards (Table 2) have been described as part of the viral communities harbored by several mosquito species in different geographic regions [41][42][43][44][45][46][47][48]. Bold type corresponds to the selected viruses for primers design.…”
Section: Virome Composition On Honey-baited Fta Cards During Entomolosupporting
confidence: 86%
“…The additional description of honeybee-infecting virus Rhopalosiphum padi virus (Dicistroviridae, genus Cripavirus) in mosquito species from Hubei, China [51] and in Culex mosquitoes from California [41], together with the assembly of sequences linked to chronic bee paralysis virus (CBPV) (unclassified ssRNA+ virus) and Apis mellifera filamentous virus (dsDNA Hytrosaviridae family) from French Anopheles maculipennis [52] and from Culex mosquitoes from California [41] respectively, suggested that these viral families could be associated to mosquitoes as well. In addition, due to the low genetic identity of these viruses with their closest honeybee counterpart, the scarcity of mosquito-based sequences available in public databases, and the continuous discovery of new picorna-like viruses in insects [41,45,50,53,54], might suggest that we are dealing with novel mosquito picorna-like viruses. Based on the abovementioned findings, captured mosquitoes that fed on the FTA cards could have been the source of the identified viruses.…”
Section: Virome Composition On Honey-baited Fta Cards During Entomolomentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have performed viral metagenomics on field mosquitoes collected from different countries (including the United States, Puerto Rico, China, Kenya, Australia, Sweden, etc. ), mainly focusing on novel virus discovery (16)(17)(18)(19)(20)(21)(22)(23)(24). Some newly discovered mosquito-specific viruses (MSVs) have been proposed as future biological control agents against arboviruses (25)(26)(27) or as novel vaccine platforms (27) or used in diagnostic assays in chimeric virus formation with structural protein genes from arboviruses (27).…”
mentioning
confidence: 99%
“…Picornaviruses (+ssRNA) feature prominently in most host-associated virome surveys [21][22][23][24][25][26][27][28][29][30][31][32] and are ubiquitous in marine plankton as free particles [33][34][35][36][37][38][39]. Of the 19 picornairus-like genome fragments recovered in this survey, 9 matched most closely to dicistroviruses (Dicistroviridae), 2 to bacillarnaviruses (Marnaviridae), and 1 to caliciviruses (Caliciviridae) by BLASTx (Fig.…”
Section: Description Of Viruses Recovered In Viral Metagenomesmentioning
confidence: 95%